Pentingnya Pengalaman Implementasi Filsafat Realisme Dalam Pengembangan Karakter Siswa Di Sekolah Dasar - Idawati, Idawati; Risani, Arni; Muslim, Muslim; Hasni, Hasni (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Religious character education must be applied at all levels of education, especially at the elementary school level. This is because elementary school students still have a simple mindset so that they have a high chance of being instilled with noble character. The philosophy of idealism has the same goal as the goal of the Republic of Indonesia, which is to form a human being who has a noble personality and has a spiritual character. However, in reality, so far the education system in elementary schools has focused more on mastering knowledge, while the aspect of religious character seems to be forgotten. The purpose of this research is to find out the cultivation of religious character education in the perspective of idealism. The results of the study state that religious character and the philosophy of idealism are closely related to morals or noble human morals.